Some new lacunary statistical convergence with ideals - Kilicman, Adem; Borgohain, Stuti (Springer Open, 2017)
In this paper, the idea of lacunary Iλ-statistical convergent sequence spaces is discussed which is defined by a Musielak-Orlicz function. We study relations between lacunary Iλ-statistical convergence with lacunary Iλ-summable sequences. Moreover, we study the Iλ-lacunary statistical convergence in probabilistic normed space and discuss some topological properties.